Law of strata pressure behavior of surrounding rock in nearby goaf roadway for extra-thick coal seams of Datong mine area - Xiaoyong Lian; Xiaoyong Lian; Chen Li; Jun Li; Liang Wu (Frontiers in Earth Science, 2023)
The nearby goaf road in the extra-thick coal seam of the Datong mining area exhibits intense strata pressure behavior, which affects the working face mining. Herein, we study the laws of the strata pressure behavior of this road in detail using various methods, including laboratory tests, theoretical analyses, numerical simulation, and field monitoring. Considering the mine pressure characteristics of the nearby goaf road, namely, roof cracking, two-side deformation, and floor heaving, the mechanical tests and theoretical failure analyses of the surrounding rock in the mining-induced non-uniform stress field were carried out. The circular-oval-butterfly failure trend of the surrounding rock in the nearby goaf road under the influence of mining was obtained. The steady failure evolution lateral pressure coefficient (λ=0.5∼1.8) and butterfly mutation lateral pressure coefficient (λ<0.35 or λ>2.1) of the surrounding rock in the nearby goaf road were analyzed. We performed numerical simulation to study the stress field and the plastic zone shape-size characteristics of the surrounding rock during excavation and mining (with or without the top extraction road), and the theoretical law of the mine pressure was obtained for the Tong Xin coal mine. Finally, field monitoring indicates that the mine pressure behavior of the nearby goaf road exhibits spatial differences, namely, the difference between the stresses of the two sides and roof, and the stress characteristics of the deep and shallow surrounding rock. The findings of this study on the mine pressure behavior in the nearby goaf road have great practical significance for targeted measures to control the surrounding rock stability.